2021
DOI: 10.1080/20002297.2021.1910462
|View full text |Cite
|
Sign up to set email alerts
|

Potential prebiotic substrates modulate composition, metabolism, virulence and inflammatory potential of an in vitro multi-species oral biofilm

Abstract: Background : Modulation of the commensal oral microbiota constitutes a promising preventive/therapeutic approach in oral healthcare. The use of prebiotics for maintaining/restoring the health-associated homeostasis of the oral microbiota has become an important research topic. Aims : This study hypothesised that in vitro 14-species oral biofilms can be modulated by (in)direct stimulation of beneficial/commensal bacteria with new potential prebiotic substrates tested at 1 M an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 105 publications
2
5
0
Order By: Relevance
“…PgA encodes a protein involved in the synthesis of a polysaccharide with an important role in aggregation and biofilm formation 63 . Similar observations for pgA expression in modulated oral biofilms were also previously observed 46 , and this could be explained as a response to external stress, something reported for other Aggregatibacter species . For F. nucleatum, downregulation was often observed for the gene encoding a hemin receptor, which is highly immunogenic and plays an important role in hemin uptake 65 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PgA encodes a protein involved in the synthesis of a polysaccharide with an important role in aggregation and biofilm formation 63 . Similar observations for pgA expression in modulated oral biofilms were also previously observed 46 , and this could be explained as a response to external stress, something reported for other Aggregatibacter species . For F. nucleatum, downregulation was often observed for the gene encoding a hemin receptor, which is highly immunogenic and plays an important role in hemin uptake 65 .…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the substrates tested in this study achieved at least one, and often both, of these goals. This shows potential for these substrates as modulators of oral biofilms, since previous studies on potential prebiotic substrates for oral health reported similar effects on multi-species biofilm composition 30,31,33,46 . The role of species like A. actinomycetemcomitans, F. nucleatum, P. gingivalis and P. intermedia in the initiation and progression of periodontal diseases has been well-characterized 11,44,47,48 .…”
Section: Discussionsupporting
confidence: 61%
“…For instance, Jansen et al ( 2021) found that P. intermedia biofilms were less susceptible than P. gingivalis biofilms, while in the current study P. intermedia was one of the most affected species in the multispecies biofilms. While the synbiotic was the driver of the biofilm change, the high prevalence of the streptococcal commensals, which also possess antagonistic potential toward the periodontal pathobionts in this model (Verspecht et al, 2021), in the synbiotic conditions is also likely to have an important role in these changes by, for example, producing hydrogen peroxide, further increasing the oxidative stress.…”
Section: Discussionmentioning
confidence: 92%
“…While most periodontal models use anaerobic conditions [9,19,20,21,22], the surface of an oral biofilm is exposed to aerobic conditions. In Verspecht et al [23], strict anaerobic species are present in oral biofilms cultured in micro-aerophilic conditions (6% O 2 ). This residence is due to the presence of anaerobic micro-environments in which anaerobic species can survive.…”
Section: Spatiotemporal Monitoring Demonstrates Prebiotic Treatment R...mentioning
confidence: 99%